A New Quality Management System in Auditing. Information and Communications - Lubenchenko, О. Е. (Statistics of Ukraine, 2022)
The purpose of the article is to provide methodological recommendations for auditing entities regarding the creation of a quality management system, in particular its element "Information system and information interaction". The results of the analysis of the ISQM International Standard 1 "Quality management in an auditing company conducting audits, review of financial statements, other assurance tasks, related services" are highlighted, and practical developments are presented. It has been proven that the formation of a quality management system requires a comprehensive risk-oriented approach to the organization and conduct of inspections, while the responsibility for quality in the audit firm is considered and controlled at two levels: at the highest – management level and at the operational level. The procedures of quality risk assessment and control measures have been developed in response to assessed risks. They are as follows: assessment of threats to ethics and determination of measures to respond to identified threats based on the working document "Identification of Threats to Independence", through annual confirmation of independence of the audit company's staff; investigations of complaints and accusations by appointing responsible persons, recording the consideration of complaints in the appropriate journal and taking measures to influence people who systematically violate the requirement for the quality of audit services; communications during the acceptance of the client and task, execution of the task, provision of auditor's reports; communication to the client's management through letters to management personnel and people with the highest authority, through a transparency report taking into account the requirements of the International Standard ISQM 1 with the provision of an additional report for the audit committee; reporting to regulatory bodies in accordance with the Law of Ukraine "On the Audit of Financial Statements and Audit Activity"; direct negotiations within the audit group and with the involvement of the client, inquiries and assessment of the responses of the client's management staff; publication of information about the quality of audit services on the websites of audit firms and in mass media; procedures for monitoring the quality of selected tasks and the quality management system as a whole.